Recommendations for Designing, Conducting and Reporting Clinical Observational Studies in Homeopathic Veterinary Medicine - Weiermayer, Petra; Frass, Michael; Fibert, Philippa; Klein-Laansma, Christien; Ulbrich-Zürni, Susanne (Homeopathy, 2023)
Background Clinical observational studies are an important methodological approach in human and veterinary research, examining and describing treatment experience with good external validity. There are currently few observational studies in the field of homeopathic veterinary medicine.Aim The aim of the study was to develop recommendations for designing, conducting and reporting observational studies in homeopathic veterinary medicine.Materials and Methods A literature review was performed using various search strategies for identifying guidelines and checklist tools relevant for observational studies, veterinary research and homeopathy. Useful guidelines were selected. Prior recommendations for designing and conducting observational studies in human homeopathic medicine were supplemented with recommendations for homeopathic veterinary medicine that were evaluated by an expert panel.Results The veterinary extension of the Strengthening the Reporting of Observational Studies in Epidemiology – Veterinary (STROBE-Vet) statement was identified as a useful tool to improve the reporting quality of observational studies, and it has been supplemented here with additional recommendations that are applicable to homeopathy. STROBE-Vet is complemented in the literature by several reports, checklists and guidelines on veterinary medicine in general, such as the Checklist for One Health Epidemiological Reporting of Evidence (COHERE) and the Animal Health Surveillance Reporting Guidelines (AHSURED). Identified items that related to laboratory animal research were excluded as non-relevant to our study.Conclusion Clinical observational studies are an important methodological approach, having currently unrealized potential in the field of homeopathic veterinary medicine. With relatively minor adjustments, the practical guidelines and checklists available to researchers in designing, conducting and reporting observational studies in human homeopathic medicine have been adapted for homeopathic veterinary medicine, for which high quality can be assured by implementing recommendations such as those in STROBE-Vet. With the emergence of the One Health concept, the COHERE checklist can be viewed with growing significance.
Keywords: clinical observational studies; homeopathic veterinary medicine; guidelines; recommendations